Negotiating Islamic Literacy and Multicultural Schooling: The Implementation of Qur'anic Education in an Indonesian Overseas School in Malaysia - Imam Hanafi; Abdul Aziz; Nurlaela (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study explores the implementation of Qur’anic education at the Indonesian School of Kota Kinabalu (Sekolah Indonesia Kota Kinabalu – SIKK) in Malaysia and its role in sustaining Islamic literacy within a multicultural educational environment. Using an intrinsic qualitative case study design, data were collected through in-depth interviews with the principal, Islamic education teacher, students, and parents, supported by participant observation and document analysis. Data were analyzed through thematic analysis, while trustworthiness was ensured through triangulation and member checking. The findings indicate that Qur’anic education at SIKK functions not only to develop students’ ability to read and write the Qur’an but also to preserve religious identity, strengthen cultural continuity, and support students’ adaptation to multicultural realities. Four themes emerged: institutional commitment to preserving religious identity, negotiation of Islamic literacy within multicultural schooling, parental involvement as co-educators, and adaptive responses to structural constraints. The study introduces the concept of the Diaspora Islamic Literacy Ecosystem, which explains how schools, families, teachers, and multicultural contexts interact to sustain Islamic literacy among diaspora students. This study contributes to the literature on Islamic education, diaspora education, and multicultural schooling by offering a new conceptual framework for understanding Qur’anic education in overseas Muslim communities.